Micro Credit and Women Empowerment: A Study on Grameen Bank’s Strategy of Poverty Alleviation - Chowdhury, Mohammed Thanvir Ahmed (i-Proclaim, 2013)
Generally, it is held that, Women economic participation is positively related to their status. It is assumed that participation changes woman’s power relationship and hence her status in the family, and thus a woman having no such access will have relatively low power and status. Relatively argued, women experience hunger and poverty in much more intensive ways than men. If one of the family members has to starve, it is an unwritten law that it has to be the mother. That is why women were targeted in the center point of micro credit program. However, the stagnation in the impact of micro credit on income may have serious implication for the success of micro finance institution and their long term sustainability and therefore the question deserves serious attention from researchers. The above concerns are related mostly to the long term impact of micro credit. Thereby we were intended to see the structures which dictate dependence press on these women. And if the gains they have made in income and assets are to be sustained, the control they have negotiated over their lives is to be maintained. In this regard, we want to see how women can build their empowerment and what Grameen Bank can do to strengthen them for poverty alleviation. JEL Classification Code: I32; E51